The contribution of content knowledge, creativity and innovation towards teacher’s self-efficacy in teaching economics subject in Sabah - Abdul Said Ambotang; Christina Andin @ Nur Qistina (2020)
The main purpose of this study is to identify the direct and indirect contribution of content knowledge, creativity and innovation to the self-efficacy of Economics subject teachers in the teaching process. The total of 536 form six students representing the entire state of Sabah were selected using simple random sampling. This study is a non-experimental quantitative study using the survey method to answer the research objectives. The questionnaire used was developed based on Shulman’s PCK theory and Bandura’s theory which is the basis of this study. The SPSS Software and AMOS are used to analyze data and path between selected variables. Multiple regression tests showed that there was a contribution of independent variables to the dependent variables. The results of the path analysis test also prove that the content knowledge, creativity and innovation of Economics teachers show a direct and indirect contribution to the level of self-efficacy of the Economics teachers. The results of the structural equation modeling (SEM) analysis after modification showed that 83.6 per cent of the independent variable variance contributed to the self-efficacy of Economics teachers. This result indicates that there is a good fit of the measurement model in the structural equation model (SEM) generated in this study.